Alat Penghitung Jumlah Gerakan Pull Up dan Push Up Menggunakan Sudut Kemiringan pada Sensor MPU6050 Berbasis Internet Of Things - Putra, Dimas Ade; Jufrizel, Jufrizel; Ullah, Aulia; Maria, Putut Son (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The pull-up and push-up counter device is designed to automatically count the number of pull-up and push-up repetitions performed by an individual. The problem faced is errors in performing pull-up and push-up movements and the limitation of manual counting, which solely relies on remembering the total count of movements from the previous day. This can lead to uncertainty in monitoring the progress of the exercise. The purpose of this research is to develop a pull-up and push-up counter device that utilizes the Internet of Things (IoT) and is connected to the Blynk application on a smartphone to provide ease and accuracy in recording exercise repetitions, eliminate the difficulties of manual counting, and provide real-time data to users for monitoring and tracking their exercise progress. This device is equipped with an MPU 6050 sensor that can detect changes in angular acceleration in the arms. The methodology applied in this research is the Research and Development (R&D) method, which includes product efficiency testing and product development. The research results show that this device can connect to Wi-Fi networks effectively, and its status can be viewed through the LCD display on the device as well as the Blynk application, which displays an online status when the device is connected and an offline status when it is not. The MPU 6050 sensor works effectively in detecting the user's inclination at the specified angles, forming a 70 angle for pull-up movements and a 90 angle for push-up movements. Testing was conducted using a comparative method between manual counting and counting using the device. In the tests conducted at three different movement speeds, it was found that fast movements in pull-ups resulted in a difference in counting of 7.6%, while in push-ups, there was a difference in counting of 6.8%. These differences were due to the device's inability to detect the intended angles of inclination accurately. On the other hand, movements at moderate and slow speeds showed a 0% difference in counting for both pull-ups and push-ups.